PEMANFAATAN SAMPAH ORGANIK MENJADI PUPUK KOMPOS DENGAN BANTUAN MIKROORGANISME DI DESA SIBETAN KARANGASEM - GUNAM, WAYAN; WRASIATI, I.B., L.P.; WIJAYA, I MD. MAHAPUTRA; ARNATA, IW.; YOGA, I W.G. SEDANA (Buletin Udayana Mengabdi, 2012)
ABSTRACT Sibetan village which located in Karangasem Regency eastern of Bali is well known for its zallaca farming, that produces high quality and original taste of zallaca fruits. Zallaca,s post harvest process in farmer’s and distributor’s level produces enough quantity of organic waste. This waste currently is become a pollutant to their neighborhood and their soil. Even tough the majority of the waste is organic, it still became a disturbance because of its large volume. Hence, a special method or treatment is needed to solve this problem. Composting this organic waste through the helps of micro-organisms is became the selected method because this process is able to decreases the volume of the organic waste, and also the fermented waste is useful as an organic fertilizer. The fermented waste add a value to the zallaca’s farmer in order to decrease the dependency to artificial fertilizer, and helps increase the income of the zallaca’s farmer with the decrease allocations of farming expenses to bought an artificial fertilizer.